Effect Of Placement And Operational Standards Procedures Regarding The Performance Of Employees Of The Office Of The Regional Representative Council Of Samarinda City - Askiah, Askiah; Anisa Maqwani Retalita Putri Periadi; Joko Sabtohadi; Muhamad Harry Rahmadi (Sean Institute, 2024)
Data held by the Secretariat of the Samarinda City Regional People's Representative Council shows that employee placement is inconsistent with educational level, workload analysis and position analysis, as well as standard operating procedures. Several changes to the organizational structure will of course also have an impact on changes to standard operating procedures. The aim of the research is to determine the effect of placement, standard operating procedures. The research method used was field research using a quantitative approach with 41 respondents, then data analysis using the SPSS 25 application. The results of the research on the placement variable obtained a t table value of 2.023, t count > t table (6.112 > 2.023), meaning that the placement variable had a significant positive influence on employee performance. The test results for the standard operational procedure variable obtained a t table value of 2.023, t count > t table (5.940 > 2.023), meaning that the standard operational procedure variable has a significant positive effect on employee performance. Then, simultaneous placement and standard operating procedures do not have a significant effect on employee performance. From the partial test results, the placement variable is the dominant variable compared to the standard operational procedure variable on employee performance. Furthermore, the R2 coefficient of determination value of 97.1% means that employee performance is influenced by placement and standard operating procedures, while the remaining 2.9% is the influence of other variables not examined in this research.